Green Chemistry Microscale Practicums on High School Students’ Learning Outcomes and Motivation: Systematic Literature Review - Wijaya, Komang Jnani; Pratiwi, Ni Kadek Mira; Redhana, I Wayan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Microscale practicums are a practicum design that utilizes small amounts of materials and tools as a solution to the limitations of school laboratories, while integrating the application of green chemistry principles in education. A number of empirical studies have reported the positive impact of implementing green chemistry-based microscale practicums. However, studies that specifically integrate green chemistry principles and analyze their integrated impact on learning outcomes and motivation among high school students are still limited and scattered. The purpose of this study is to systematically examine how the application of green chemistry-based microscale practicums can improve learning outcomes and motivation among high school students. This study uses the Systematic Literature Review (SLR) method with the PRISMA model through searching for articles on Google Scholar, GARUDA, DOAJ, and SCOPUS. The articles analyzed were adjusted to the inclusion criteria, namely empirical studies published between 2005 and 2025 with high school/MA students as subjects and focusing on the effect of green chemistry-based microscale practicums on student learning outcomes and motivation. A total of 10 articles met the inclusion criteria and were analyzed in this study. The synthesis results show that this approach consistently improves student learning outcomes in terms of concept understanding, achievement, science process skills, and student memory retention, as well as learning motivation through increased interest and enthusiasm for learning. These findings provide evidence-based guidance for chemistry teachers and curriculum developers in designing environmentally friendly laboratory learning that is effective in improving students’ cognitive and affective achievements.